Research paper Enriching Language Acquisition of Preschool Children from Low-SES Through Shared Story Reading - Nayereh zamani; Saeid Hassanzadeh; Mohsen Shokoohi-Yekta (Ravānshināsī-i Afrād-i Istis̠nāyī, 2020)
Abstract Early intervention is important to minimize persistent difficulties in language and its related domains in  preschool children with or at-risk of language impairment. The purpose of this study was to investigate the effectiveness of shared story reading program on the development of language skills of preschool children of low socioeconomic status. This study adopted a quasi- experimental research design with pretest-posttest-follow-up and a control group. From two preschool centers in Ahmadabad Mostofi town during a multi-level screening process, 30 children whose language test scores were below the standard deviation (70-85) were selected, being diagnosed for language problems. They were randomly assigned to the experimental and control groups. Subjects in the experimental group (n=15) were further divided into four smaller groups, received 30 shared story reading program intervention sessions, each session lasting 45 minutes three days a week. Data were collected through Test of Language Development and Narrative. Data analysis was performed by using the Repeated Measures MANOVA. The results indicated a significant effect (P=0/001) of the program on increase of semantic knowledge, syntactic knowledge, and language development in general, and improvement of narrative writing in the experimental group. Post-test and follow-up differential scores also approved the effectiveness of the shared story reading program. Accordingly, the shared story reading program is recommended as a preventive program, potentially bridging the word gap for at-risk children.